Fe removal by adsorption using ash from oil palm factory - Isa, M.H.; Al-Madhoun, W.A.; Aziz, H.A.; Asaari, F.A.H.; Sabiani, N.H.M. (2004)
Heavy metals are often present in water and wastewater as contaminants. From the public health and environmental protection point of view, it is important that their concentrations be limited to permissible levels. Technologies for heavy metals removal include ion exchange, chemical precipitation, reverse osmosis, etc. which are often ineffective or expensive. Adsorption is a commonly used method for the removal of heavy metals from aqueous solutions. However, for the process to be economical, the adsorbent should be easily and cheaply available in abundance and it should require minimal or no pre-treatment; for expensive pre-treatment procedures would add to the overall treatment cost. The present study focuses on iron (Fe) removal by adsorption using oil palm by-products (fibre, shell, ash) without pre-treatment or activation. The results show that among the materials tested, ash was the most effective adsorbent. The optimum agitation time and optimum pH were 90 minutes and 5 respectively. The removal followed the Freundlich isotherm closely with R2 = 0.9479. Desorption of over 98 % was achieved with 0.15 N HCl.